Analysis of quantitative PCR for the diagnosis of deletion and duplication carriers in the dystrophin gene. Issue 3 (March 1992) - Abbs, S; Bobrow, M
Abstract : A direct, non-radioactive method of quantitative PCR amplification has been investigated for the diagnosis of deletion and duplication carriers in the dystrophin gene. The simultaneous amplification of two loci, or several loci using multiplex PCR, allows for the direct comparison of relative amounts of products from normal homozygous loci and potentially heterozygous deleted/duplicated loci. Sufficient cycles of PCR are performed to enable visual analysis or densitometric quantification of products on ethidium bromide stained gels. The method has been verified in blind trials performed on known genotypes and by showing that under the conditions used the assay remains within the exponential phase of amplification.